Access to the tracheal pulmonary pathway in small rodents - Ribeiro,Roberto S. A. (2015)
ABSTRACT The tracheal pulmonary route is used in diverse experimental models for the study of drugs, infectious agents, and diseases. In view of its importance and associated difficulties, the present article proposes to give research groups up-to-date information on techniques to access the tracheal pulmonary pathway of small rodents.